Design and development PolyLactic Acid (PLA) recycling machine for 3D printer - Chee Kiong, Sia; Amali Firdaus Saini (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study explores the PLA Filament Recycling Machine. The main purpose of this study is to design and develop a filament recycling machine for indoor usage that is user-friendly, low in pollution, and simple to maintain. In order to accomplish the goal and solve the waste filament issue, a new design idea must be developed. The design method of G.E. Dieter has been selected for this study. It includes a number of significant processes, including idea creation, concept evaluation, configuration design, and detail design. Concept development is a way for diverging the concept. Then, the concept evaluation selects the most efficient idea. The role of the design idea is discussed throughout the configuration design process. In the last step, which is detail design, Solidworks 2021 CAD software is used to create all the detail drawings. Finally, it is hoped that this innovative design for a filament recycling machine would take the filament recycling machine to the next level.